Comparison of Osseointegration of Five Different Surfaced Titanium Implants - Dundar, Serkan; Yaman, Ferhan; Bozoglan, Alihan; Yildirim, Tuba Talo; Kirtay, Mustafa; Ozupek, Muhammet Fatih; Artas, Gokhan (Lippincott Williams & Wilkins, 2018)
The topography, chemical features, surface charge, and hydrophilic nature of titanium implant surfaces are crucial factors for successful osseointegration. This study aimed to investigate the bone implant contact (BIC) ratio of titanium dental implants with different surface modification techniques using the rat femoral bone model. Sandblasted and acid washed (SL-AW), sandblasted (SL), resorbable blast material (RBM), microarc (MA), and sandblasted and microarc (SL-MA) surfaces were compared in this study. Forty male Sprague-Dawley rats were used in this study. The rats were divided into 5 equal groups (n = 8), and totally 40 implants were integrated into the right femoral bones of the rats. The rats were sacrificed 12 weeks after the surgical integration of the implants. The implant surface-bone tissue interaction was directly observed by a light microscope, and BIC ratios were measured after the nondecalcified histological procedures. Bone implant contact ratios were determined as follows: SL-AW: 59.26 +/- 14.36%, SL: 66.01 +/- 9.63%, RBM: 63.53 +/- 11.23%, MA: 65.51 +/- 10.3%, and SL-MA: 68.62 +/- 6.6%. No statistically significant differences were found among the 5 different surfaced titanium implant groups (P > 0.05). Our results show that various implant surface modification techniques can provide favorable bone responses to the BIC of dental implants.
23rd International Dental Congress of the Turkish-Dental-Association -- SEP 21-24, 2017 -- Istanbul, TURKEY
Keywords: Bone; bone implant connection; dental implant surfaces; osseointegration; rat femur